Pengaruh Jenis Tepung terhadap Kandungan Gizi Kerang Darah (Granosa) Petis - Markus P. Miten Hurit; Yosephina M. J. Batafor; Karolus Banda Larantukan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Blood cockles are an abundant fishery commodity. However, blood cockles are only processed for their meat, so diversification of products in shellfish processing has been carried out, namely petis, which uses broth from boiling the shellfish meat. This study aims to determine the effect of using various types of flour on the nutritional content of blood cockle petis. The method used in this study was an experimental method with a quantitative descriptive approach. This study was conducted through the stages of making shellfish broth as a raw material and the stages of petis production, followed by proximate tests to determine the water, ash, protein, fat, and carbohydrate content. The results of the study showed that the addition of different types of flour, namely wheat flour, tapioca flour, and glutinous rice flour to blood cockle petis had a significant effect on the water content of blood cockle petis with the addition of wheat flour, tapioca flour, and glutinous rice flour, namely 61.785%, 75.075%, 68.442%, ash content of 1.388%, 0.598%, 0.703%, protein content of 6.226%, 4.964%, 6.669%, fat content of 0.932%, 0.876%, 1.292%, and carbohydrate content of 91.454%, 93.562%, 91.336%.